2001
DOI: 10.1021/jo001792i
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular C−H Insertion Reactions of (η5-Cyclopentadienyl)dicarbonyliron Carbene Complexes:  Scope of the Reactions and Application to the Synthesis of (±)-Sterpurene and (±)-Pentalenene

Abstract: (eta(5)-Cyclopentadienyl)dicarbonyliron carbene complexes, [(eta(5)-C(5)H(5))(CO)(2)Fe=CHR](+)BF(4)(-), are generated as reactive intermediates from thioether derivatives, (eta(5)-C(5)H(5))(CO)(2)FeCH(R)SPh, by S-alkylation with trimethyloxonium tetrafluoroborate and loss of thioanisole. The carbene complexes undergo intramolecular C-H insertion into appropriately situated side chains to form cyclopentane derivatives. The reaction has been developed into a general procedure employing cycloalkanones as scaffold… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…The same authors investigated the selectivity of this process in further studies and explained the observed reaction outcome via a concerted C-H insertion reaction that proceeds via a chair-like cyclic transition state (12, Scheme 5) [29,30]. (13,14) by Helquist and coworkers [29,30].…”
Section: Stoichiometric C-h Functionalizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The same authors investigated the selectivity of this process in further studies and explained the observed reaction outcome via a concerted C-H insertion reaction that proceeds via a chair-like cyclic transition state (12, Scheme 5) [29,30]. (13,14) by Helquist and coworkers [29,30].…”
Section: Stoichiometric C-h Functionalizationmentioning
confidence: 99%
“…The direct C-H functionalization of benzene or alkyl benzenes (15) via carbene or metal-carbene intermediates can give access to three different products, which arise from (a) insertion into a C(sp 2 )-H bond (17), (b) insertion into a side-chain C(sp 3 )-H bond (18), or (c) a cycloaddition reaction Scheme 5. Intramolecular C-H insertion reactions for the synthesis of cyclopentane derivatives (13,14) by Helquist and coworkers [29,30].…”
Section: C-h Functionalization Reactions Of Aromatic C-h Bondsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include copper [36][37][38][39][40][41][42][43][44][45], silver [46,47], iron [48][49][50], gold [40], and magnesium [51,52], and most will be discussed in context, particularly in Sect. 3.1.…”
Section: Fig 3 Chiral Dirhodium Catalysts Discussed In This Chaptermentioning
confidence: 99%
“…[5][6][7][8][9][10] Seminal studies started with the intramolecular functionalization of CÀ H bonds using stoichiometric amounts of a preformed iron-carbene compound. [5] Subsequent reports allowed the functionalization of strong CÀ H bonds (> 95 kcal • mol À 1 ) in both stoichiometric and catalytic fashion but applying harsh reaction conditions (Scheme 1a) [6] that are also compatible with decomposition of the diazo reagent, resulting in uncatalyzed CÀ H insertion. [7] Most importantly, these studies pinpoint to high energetic barriers for the iron mediated Csp 3 À H insertion reactions, which have limited the scope to relatively weak CÀ H bonds.…”
Section: Introductionmentioning
confidence: 99%